Proses dan Dinamika Penyusunan Undang-Undang Nomor 18 Tahun 2012 tentang Pangan - Achmad Suryana; Munawar Khalil (Forum penelitian Agro Ekonomi, 2017)
Legal drafting of the Food Law (Number 18/2012) was initiated by DPR RI using its initiative right. This law was issued in 2012 to replace the existing Food Law (Number 7/1996) because it was considered to be incapable to provide guidance for solving problems and challenges of national food development. This condition was due to significant changes in national and international strategic environment. Legal drafting processes of this law accommodated not only views of the parliament members of Working Committee representing their parties and the national government representatives coordinated by Ministry of Agriculture, but also from people’s aspirations through public consultations. From all subjects discussed, several issues were needed more intensive attentions, i.e. (a) meaning of food sovereignty, (b) position of imports to support food availability, (c) national food institution establishment, and (d) halal food issue. This paper aimed to write down processes and dynamics of legal drafting of this food law with those four issues as examples. It is expected that this article will be useful as information and lessons learned about legal drafting process and help stakeholders of food development to have more understanding of real meaning and intention of norms written in this Law. AbstrakPenyusunan Undang-Undang (UU) Nomor 18 Tahun 2012 tentang Pangan diinisiasi DPR RI dengan menggunakan hak inisiatif. UU Pangan ini diterbitkan tahun 2012 mengganti UU Pangan yang ada waktu itu (No. 7/1996) yang dinilai sudah tidak mampu memberikan acuan untuk menjawab berbagai permasalahan dan tantangan pembangunan pangan nasional. Kondisi ini disebabkan oleh terjadinya perubahan yang signifikan  dari lingkungan strategis nasional dan internasional. Proses penyusunan UU Pangan ini tidak saja mengakomodasi pemikiran para anggota DPR dari Panitia Kerja RUU Pangan yang mewakili fraksinya dan wakil-wakil kementerian/lembaga pemerintah yang dikoordimir oleh Kementerian Pertanian, tetapi juga menampung berbagai aspirasi masyarakat melalui penyelenggaraan konsultasi publik. Dari keseluruhan materi yang dibahas dalam RUU Pangan, beberapa substansi memerlukan pembahasan yang lebih intens dan mendalam, empat isu diantaranya adalah: (a) pengertian kedaulatan pangan; (b) posisi impor dalam penyediaan pangan; (c) pembentukan kelembagaan pangan; dan (d) kehalalan pangan. Penulisan artikel ini bertujuan untuk mendokumentasi proses dan dinamika pembahasan UU Pangan, dengan pendalaman menggunakan empat isu tersebut di atas. Diharapkan tulisan ini bermanfaat sebagai informasi dan pelajaran berharga mengenai dinamika penyusunan UU Pangan, dan dapat membantu pemangku kepentingan pembangunan pangan lebih memahami arti sesungguhnya dan maksud dari norma-norma yang tercantum dalam UU Pangan ini.